1967
DOI: 10.1002/hlca.19670500121
|View full text |Cite
|
Sign up to set email alerts
|

2(3H)‐Oxazolone durch Photoumlagerung von 3‐Hydroxyisoxazolen. Synthese von Muscazon

Abstract: Auch 5-Methyl-3-hydroxy-isoxazol (6), 2%: = 206 nm, dessen Herstellung bisher nicht gegliickt war3) und wofur wir im experimentellen Teil eine ergiebige und einfache Synthese beschreiben4), liess sich photochemisch zu 5-Methyl-2 (3 H)-oxazolon (7) umlagern (NMR.-spektroskopische Analyse). Die laufende Analyse der Belichtungsprodukte von 4,5-Dimethyl-3-hydroxy-isoxazol (8) [lo] zeigte, dass das Ausgangsmaterial nach zwei Stunden verschwunden war, ohne dass das erwartete 4,sDimethyl-2 (3H)-oxazolon (9) nachgewi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1971
1971
2005
2005

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The major product was indeed 5-methyl-4-oxazolin-2-one (IX), and its NMR spectrum was identical with that reported by Goth et al 8) Other products were not identified. Again, we could not isolate the ulactam (VIII), nor could we confirm the formation of acetoacetamide or acetic acid.…”
Section: Please Scroll Down For Articlementioning
confidence: 52%
See 1 more Smart Citation
“…The major product was indeed 5-methyl-4-oxazolin-2-one (IX), and its NMR spectrum was identical with that reported by Goth et al 8) Other products were not identified. Again, we could not isolate the ulactam (VIII), nor could we confirm the formation of acetoacetamide or acetic acid.…”
Section: Please Scroll Down For Articlementioning
confidence: 52%
“…3-7 I This general rule has been extended to 3-hydroxyisoxazoles by Goth et al, 8) who showed that ibotenic acid and 3-hydroxy-5-methylisoxazole are converted by ultraviolet light to muscazone and 5-methyl-4-oxazolin-2-one, respectively; the latter compound was not isolated, but was determined by NMR spectrometry of the reaction mixture.…”
Section: Please Scroll Down For Articlementioning
confidence: 96%
“…This novel product is most likely formed by a vinylcyclopropane-like rearrangement of the intermediate α- lactam (Scheme ). This type of rearrangement was postulated for several α-lactams that were accessed photochemically, but has not been observed previously for α-lactams generated chemically. It is likely that these rearrangements have been missed in most solution phase α-lactam studies because unsaturated α-lactams are relatively rare and because nucleophiles are usually present in the reaction mixture.…”
Section: Resultsmentioning
confidence: 80%
“…The major metabolic pathways via the formation of HPI to 5-phenyl-4-oxazolin-2-one, benzoylacetamide and benzoic acid are also observed in the mammalian metabolism either in vivo 3 ) or in vitro.22) Additionally, the isolation of muscazone along with ibotenic acid from Amanita muscaria 23 ) has suggested the rearrangement of the isoxazole ring to the corresponding oxazolinone by biochemical means. 24 ) All together, the disclosed major metabolic pathways of isoxathion in soil must be involved in those in a wide variety of living things.…”
Section: Discussionmentioning
confidence: 99%